High-toughness ionic gel and preparation method thereof
By introducing ethylene glycol into the polyvinyl alcohol matrix and using low-temperature frozen crystallization and ionic liquid salting treatment, the strength and toughness of the gel are improved, the problem of insufficient mechanical properties of traditional hydrogels is solved, and high strength and tough ion coagulation is achieved The development of glue has impact resistance, puncture resistance and bullet resistance, and is suitable for bulletproof materials and flexible electronic equipment.
Patent Information
- Application Number
- CN202411402364.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Traditional hydrogels have shortcomings in mechanical properties and impact resistance, which limits their use in high-demand application scenarios. There are few researches on existing high-strength and tough ionic gel materials, which are difficult to meet the needs of bulletproof materials and flexible electronic equipment. .
Ethylene glycol is introduced into the polyvinyl alcohol matrix and low-temperature freezing crystallization and ionic liquid salting treatment are used to improve the strength and toughness of the gel. Through polymerization of 70~160 degrees Celsius, freezing crystallization of -80~-20 degrees Celsius and 0~100 Fixed-saltration/direct-saltration of degrees Celsius to obtain high strength ionic gel.
The strength and toughness of the gel are significantly improved, with mechanical properties reaching a strength of 27.74 MPa and a toughness of 133.96 MPa/cubic meter. The maximum static puncture force is 110.31 N/m, the maximum puncture energy is 1.40 joules/m, and the maximum dynamic puncture is The force is 259.31 N/m, the maximum puncture energy is 2.93 J/m, and it has impact, puncture and bullet resistance.
Smart Images

Figure CN119241971A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-toughness polymer materials, and specifically relates to a high-toughness ion gel and a preparation method thereof. The ion gel is a high-toughness organic ion gel with impact resistance, puncture resistance and bullet resistance. Background Art
[0002] In recent years, with the continuous advancement of science and technology and the increasing demand for high-performance materials, high-strength and tough polymer materials have gradually attracted widespread attention. High-strength and tough polymer materials not only have important applications in the field of structural materials, but also show great potential in the fields of flexible electronics, medical equipment and protective materials. Among them, ion gel, as a new functional material, has become a research hotspot due to its excellent mechanical properties, flexibility and good conductivity. However, traditional gels still have many shortcomings in strength and toughness, which limits their use in high-demand application scenarios.
[0003] Traditional hydrogels are widely used in medical dressings and tissue engineering due to their excellent biocompatibility and simple preparation process. However, hydrogels have poor mechanical properties and structural stability. In the prior art, a Chinese patent with publication number CN114350080A discloses a hydrogel sensor and a preparation method thereof, which improves the sensitivity to weak pressure by constructing a microstructure on the surface of the hydrogel, but still has deficiencies in mechanical properties and impact resistance.
[0004] Judging from the patents currently published, there are few studies on high-strength and tough ion gel materials with excellent mechanical properties and structural stability. The development of high-strength and tough ion gel materials can not only further promote their application in bulletproof materials and flexible electronic devices, but also meet the urgent demand for high-performance materials in more fields. Summary of the invention
[0005] The present invention proposes an innovative gel strengthening strategy, which significantly improves the strength and toughness of the gel by introducing ethylene glycol into the polyvinyl alcohol matrix and using low-temperature freezing crystallization and ionic liquid salting-out treatment. Through systematic research on the preparation process and performance, it provides new ideas and technical support for the development and application of high-performance ion gel materials.
[0006] Specifically, the present invention is achieved through the following technical solutions: A high-strength and tough ion gel, which is a product obtained by polymerizing ethylene glycol and polyvinyl alcohol at 70 to 160 degrees Celsius, freezing and crystallizing at -80 to -20 degrees Celsius, and finally fixing-salting out / directly-salting out at 0 to 100 degrees Celsius.
[0007] Furthermore, the high-strength and tough ion gel is a product obtained by polymerizing ethylene glycol and polyvinyl alcohol at 70 to 160 degrees Celsius (for example, 70 degrees Celsius, 75 degrees Celsius, 80 degrees Celsius, 85 degrees Celsius, 90 degrees Celsius, 95 degrees Celsius, 100 degrees Celsius, 105 degrees Celsius, 110 degrees Celsius, 115 degrees Celsius, 120 degrees Celsius, 125 degrees Celsius, 130 degrees Celsius, 135 degrees Celsius, 140 degrees Celsius, 145 degrees Celsius, 150 degrees Celsius, 155 degrees Celsius or 160 degrees Celsius), and then freezing and crystallizing at -80 to -20 degrees Celsius (for example, -80 degrees Celsius, -75 degrees Celsius, -70 degrees Celsius, -60 degrees Celsius, -50 degrees Celsius, -40 degrees Celsius, -30 degrees Celsius or -20 degrees Celsius).
[0008] A method for preparing any of the above-mentioned high-toughness ion gels, the method comprising the following steps: a) stirring polyvinyl alcohol and ethylene glycol at 70 to 160 degrees Celsius for 1 to 6 hours to obtain a mixed solution; b) pouring the mixed solution obtained in step a) into a mold and freezing it at -80 to -20 degrees Celsius for 1 to 72 hours to obtain an organic ion gel; c) placing the organic ion gel in step b) into 1-400 ml of ionic liquid for fixation-salting out or direct-salting out to obtain a high-strength and tough ion gel.
[0009] Further, in step a), the mass ratio of the ethylene glycol to the polyvinyl alcohol is 1 to 50: 1. For example, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1, 16: 1, 17: 1, 18: 1, 19: 1, 20: 1, 30: 1, 40: 1 or 50: 1.
[0010] Further, in step c), the ionic liquid is an amino acid salt ionic liquid, an imidazolium salt ionic liquid, a pyridinium salt ionic liquid or a phospholipid salt ionic liquid; preferably, the ionic liquid is an imidazolium salt ionic liquid; preferably, the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate.
[0011] Furthermore, in step c), the fixation-salting out of the high-toughness ion gel is carried out by stretching the gel by 0% to 500%, fixing it on an acrylic plate with a clip and placing it in the ionic liquid.
[0012] Furthermore, in step c), the direct salting out of the high-toughness ion gel is performed by directly placing the gel into the ionic liquid.
[0013] Further, in step c), the volume ratio of the ionic liquid to the organogel is 1-40:1; preferably, the volume ratio of the ionic liquid to the organogel is 10:1; preferably, the volume ratio of the ionic liquid to the organogel is 20:1; more preferably, the volume ratio of the ionic liquid to the organogel is 30:1; more preferably, the volume ratio of the ionic liquid to the organogel is 40:1.
[0014] In one embodiment of the present invention, the high-strength and tough ion gel has excellent mechanical properties, with a strength of 27.74 MPa, which is 15.4 times that before salting out, and a toughness of 133.96 MPa / m3, which is 24.3 times that before salting out.
[0015] In one embodiment of the present invention, the high-toughness ion gel has a maximum static puncture force of 110.31 N / m and a maximum puncture energy of 1.40 J / m.
[0016] In one embodiment of the present invention, the high-toughness ion gel has a maximum dynamic puncture force of 259.31 N / m and a maximum puncture energy of 2.93 J / m.
[0017] In one embodiment of the present invention, the high-strength and tough ion gel is a product obtained by polymerizing ethylene glycol and polyvinyl alcohol at 70 to 160 degrees Celsius, freezing and crystallizing at -20 to -80 degrees Celsius, and finally fixing-salting out / directly-salting out at 0 to 100 degrees Celsius.
[0018] In one embodiment of the present invention, the fixation-salting out of the high-toughness ion gel is carried out by stretching the gel by 0% to 500%, fixing it on an acrylic plate with a clip, and placing it in an ionic liquid.
[0019] In one embodiment of the present invention, the direct salting-out of the high-toughness ion gel is performed by directly placing the gel into an ionic liquid.
[0020] In one embodiment of the present invention, a high-toughness ion gel specifically refers to a high-toughness organic ion gel with impact resistance, puncture resistance and bullet resistance, and its preparation method comprises the following steps: (1) stirring polyvinyl alcohol and ethylene glycol at 70 to 160 degrees Celsius for 1 to 6 hours to mix uniformly to obtain a mixed solution; (2) pouring the mixture obtained in step 1) into a mold and freezing it at -80 to -20 degrees Celsius for 1 to 72 hours to obtain an organic ion gel; (3) The organic ion gel in step 2) is placed in 1-400 ml of ionic liquid for fixation-salting out or direct-salting out to obtain a high-strength and tough ion gel.
[0021] In one embodiment of the present invention, in the high-toughness ion gel, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 1~50:1; preferably, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 20:1; preferably, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 10:1; more preferably, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 20:3; more preferably, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 5:1; more preferably, the mass ratio of the ethylene glycol to the polyvinyl alcohol is 4:1.
[0022] In one embodiment of the present invention, the high-toughness ion gel, the volume ratio of the ionic liquid to the organic gel is 1~40:1; preferably, the volume ratio of the ionic liquid to the organic gel is 10:1; preferably, the volume ratio of the ionic liquid to the organic gel is 20:1; more preferably, the volume ratio of the ionic liquid to the organic gel is 30:1; more preferably, the volume ratio of the ionic liquid to the organic gel is 40:1.
[0023] Beneficial effects: The invention discloses a high-strength and toughness ion gel and a preparation method thereof. The prepared high-strength and toughness ion gel has excellent mechanical properties, including a strength of 27.74 MPa and a toughness of 133.96 MPa / m3, which are 15.4 times and 24.3 times of those before salting out, respectively; a maximum static puncture force of 110.31 N / m, and a maximum puncture energy of 1.40 J / m; a maximum dynamic puncture force of 259.31 N / m, and a maximum puncture energy of 2.93 J / m. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The tensile stress-strain curves of high-strength and tough ion gel before and after salting out; Figure 2 The tensile stress-strain curves of high-strength and tough ion gel with different pre-stretching and salting-out conditions; Figure 3 The tensile stress-strain curves of high-strength and tough ion gel under different salt solutions; Figure 4 This is the static puncture resistance curve of high-toughness ion gel; Figure 5 This is the dynamic anti-puncture curve of high-strength and tough ion gel. DETAILED DESCRIPTION
[0025] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings: A. The specific method for measuring the tensile properties of ion gel is as follows: The tensile tests were performed on an MTS (MTS Standard 43). For the tensile tests, the dimensions of the tested ion gel were 60 × 10 × 0.5 mm. During the tests, the tensile rate was set to one thousandth of the effective length of the sample (e.g. Figure 1 , Figure 2 , Figure 3 ).
[0026] B. The specific method for measuring the static puncture resistance of ion gel is as follows: Quasi-static penetration tests were performed on an MTS device (MTS Standard 43). A rod-shaped loading head (diameter: 4 mm) with a hemispherical tip was approached at a constant speed of 10 µm / s until penetration (e.g. Figure 4 ).
[0027] C. The specific method for measuring the dynamic puncture resistance of ion gel is as follows: The heavy object drop impact test was carried out on a drop weight device (ZCJ1302-a, MTS, USA). A rod-shaped impactor (diameter: 5 mm, 0.796 kg) with a hemispherical end was dropped freely from a height of 30 cm toward the center of the sample. The impact force-displacement curve was calculated based on the acceleration signal. The thickness of the polyvinyl alcohol ion gel was measured by a digital micrometer (Sanliang Company, 0-25 mm) (e.g. Figure 5 ).
[0028] In this embodiment and its comparative example, polyvinyl alcohol is used as the matrix. The polyvinyl alcohol is produced by Aladdin and has a molecular weight of 205,000.
[0029] Embodiment 1: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) Pour the mixture obtained in step (1) into a mold and freeze it at -25 degrees Celsius for 12 hours to obtain an organogel.
[0030] Embodiment 2: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organic gel in step (2) is placed in 400 ml of 1-butyl-3-methylimidazolium tetrafluoroborate for direct salting out to obtain a high-strength ion gel.
[0031] Embodiment 3: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 0%, fixed on an acrylic plate with a clamp, and placed in 400 ml of 1-butyl-3-methylimidazolium tetrafluoroborate for fixation-salting out to obtain a high-strength ion gel.
[0032] Embodiment 4: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 25%, fixed on an acrylic plate with a clamp, and placed in 400 ml of 1-butyl-3-methylimidazolium tetrafluoroborate for fixation-salting out to obtain a high-strength ion gel.
[0033] Embodiment 5: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 50%, fixed on an acrylic plate with a clamp, and placed in 400 ml of 1-butyl-3-methylimidazolium tetrafluoroborate for fixation-salting out to obtain a high-strength ion gel.
[0034] Embodiment 6: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 75%, fixed on an acrylic plate with a clamp, and placed in 400 ml of 1-butyl-3-methylimidazolium tetrafluoroborate for fixation-salting out to obtain a high-strength ion gel.
[0035] Embodiment 7: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 0%, fixed on an acrylic plate with a clamp, and placed in 400 ml of saturated sodium chloride for fixation-salting out to obtain a high-strength and tough ion gel.
[0036] Embodiment 8: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 0%, fixed on an acrylic plate with a clamp, and placed in 400 ml of saturated sodium citrate for fixation-salting out to obtain a high-strength ion gel.
[0037] Embodiment 9: (1) 25 g of polyvinyl alcohol and 100 ml of ethylene glycol were stirred at 130 degrees Celsius for 3 hours to obtain a mixed solution; (2) pouring the mixture obtained in step (1) into a mold and freezing it at -25 degrees Celsius for 12 hours to obtain an organogel; (3) The organogel in step (2) was pre-stretched by 0%, fixed on an acrylic plate with a clamp, and placed in 400 ml of saturated ammonium sulfate for fixation-salting out to obtain a high-strength ion gel.
[0038] Figure 1 The tensile stress-strain curves of the organogels and ion gels prepared in Examples 1 to 3. The ion gel of Example 3 has the best mechanical properties, showing a high tensile strength of 27.74 MPa and a toughness of 133.96 MJ / m3.
[0039] Figure 2 The tensile stress-strain curves of the ion gels with different pre-stretching and salting-out prepared in Examples 3 to 6. As the pre-stretching degree increases, the Young's modulus and strength of the ion gel continue to increase, and the fracture strain decreases accordingly.
[0040] Figure 3 The tensile stress-strain curves of the ion gels prepared by different salt solutions in Examples 3, 7-9. The results show that the ion gels salted out using 1-butyl-3-methylimidazolium tetrafluoroborate have the strongest mechanical properties. This shows that the choice of salt solution has a significant effect on the final mechanical properties of the ion gel, and salting out using 1-butyl-3-methylimidazolium tetrafluoroborate is an effective choice for improving the performance of the ion gel.
[0041] Figure 4 The static puncture diagram of the high-toughness ion gel prepared in Examples 2 and 3 compared with Kevlar. The diagram shows that the ion gel of Example 3 performs better in static puncture resistance and energy dissipation, exceeding the performance of Kevlar.
[0042] Figure 5 The dynamic puncture diagram of the high-strength and tough ion gel prepared in Examples 2 and 3 compared with Kevlar shows that the ion gel of Example 3 has higher dynamic puncture resistance and energy dissipation. The fixed-salting out ion gel exhibits stronger puncture resistance, far exceeding Kevlar fiber of the same thickness. This excellent puncture strength is mainly due to the highly entangled structure formed by the polyvinyl alcohol chain during the salting out process.
[0043] In summary, the present invention provides new ideas and technical support for the development and application of high-performance ion gel materials. This new type of high-strength and high-toughness ion gel material will show great potential in bulletproof materials, flexible electronic devices and other high-demand application scenarios.
[0044] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-toughness ion gel, characterized in that: The high-strength and tough ion gel is a product obtained by polymerizing ethylene glycol and polyvinyl alcohol at 70 to 160 degrees Celsius, freezing and crystallizing at -80 to -20 degrees Celsius, and finally fixing-salting out or directly-salting out at 0 to 100 degrees Celsius.
2. The high-toughness ion gel according to claim 1, characterized in that: The mass ratio of ethylene glycol to polyvinyl alcohol in the high-toughness ion gel is 1-50:
1.
3. The high-toughness ion gel according to claim 1, characterized in that: The high-strength and tough ion gel is a product obtained by polymerizing ethylene glycol and polyvinyl alcohol at 130 degrees Celsius, freezing and crystallizing at -25 degrees Celsius, and finally fixing and salting out at 40 degrees Celsius.
4. The high-toughness ion gel according to claim 1 or 3, characterized in that: The fixation-salting out of the high-strength and tough ion gel is carried out by pre-stretching the gel by 0% to 500%, fixing it on an acrylic plate with a clip, and placing it in an ionic liquid.
5. The high-toughness ion gel according to claim 1 or 3, characterized in that: The direct salting out of the high-toughness ion gel is carried out by directly placing the gel into the ionic liquid.
6. A method for preparing the ion gel according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: a) stirring polyvinyl alcohol and ethylene glycol at 70 to 160 degrees Celsius for 1 to 6 hours to obtain a mixed solution; b) pouring the mixed solution obtained in step a) into a mold and freezing it at -80 to -20 degrees Celsius for 1 to 72 hours to obtain an organic ion gel; c) placing the organic ion gel in step b) into 1-400 ml of ionic liquid for fixation-salting out or direct-salting out to obtain a high-strength and tough ion gel.
7. The method according to claim 6, characterized in that: In step a), the mass ratio of the ethylene glycol to the polyvinyl alcohol is 1-50:
1.
8. The method according to claim 6, characterized in that: In step c), the ionic liquid is an amino acid salt ionic liquid, an imidazolium salt ionic liquid, a pyridinium salt ionic liquid or a phospholipid salt ionic liquid.
9. The method according to claim 6, characterized in that: In step c), the volume ratio of the ionic liquid to the organogel is 1-40:1.
Citation Information
Patent Citations
Hydrogel sensor and preparation method thereof
CN114350080A
Polyvinyl alcohol gel medium used for recycling explosion fragments and shooting bullets as well as preparation method and applications thereof
CN102174237A
Wide-temperature organic hydrogel dressing and preparation method thereof
CN109157671A
Super-tough anti-freezing polyvinyl alcohol hydrogel and preparation method thereof
CN113150317A
Preparation method for synthesizing gelatin material by carboxyl functionalized polyimidazole ionic liquid
CN118388799A
